Initial Reports of the Deep Sea Drilling Project 1985
DOI: 10.2973/dsdp.proc.80.146.1985
|View full text |Cite
|
Sign up to set email alerts
|

Organic and Inorganic Nitrogen in Sediments from Leg 80, Deep Sea Drilling Project

Abstract: Concentrations of organic and inorganic nitrogen have been measured on Leg 80 sediments. The inorganic nitrogen content is relatively constant, 0.02-0.03 wt.%. Because most of the inorganic nitrogen occurs as NH 3 or (NH 4) + fixed on clays, clay-poor sediments have lower inorganic nitrogen contents. Organic nitrogen content depends upon both the type and the quantity of organic matter present. In Leg 80 sediments, woody kerogens contain much less organic nitrogen than do kerogens of algal origin. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…Reduced-C concentrations and d 13 C also decrease slightly with increasing depth in the upper 150 m of site 1149, contributing to a subtle down-section trend in C reduced /N, and indicating some parallel behavior throughout the organic reservoir. Together, the shifts in reduced C, total N, and C reduced /N with increasing depth at Site 1149 are compatible with the shifts in the same parameters over similar depth horizons reported for other Pacific Ocean deep-sea sediment cores and attributed to diagenesis [Muller, 1977;Waples and Sloan, 1980;Waples, 1985] (unfortunately, N and C isotope data were not obtained in these previous studies). A full explanation of these organic geochemical phenomena, and a more comprehensive reconstruction of diagenesis in this section, would require analyses of separated organic and inorganic N fractions (see studies by Muller [1977], Waples and Sloan [1980], and Williams et al [1995]) and a more comprehensive consideration of the chemical compositions of the interstitial waters from the sediment cores.…”
Section: Diagenetic Processessupporting
confidence: 89%
“…Reduced-C concentrations and d 13 C also decrease slightly with increasing depth in the upper 150 m of site 1149, contributing to a subtle down-section trend in C reduced /N, and indicating some parallel behavior throughout the organic reservoir. Together, the shifts in reduced C, total N, and C reduced /N with increasing depth at Site 1149 are compatible with the shifts in the same parameters over similar depth horizons reported for other Pacific Ocean deep-sea sediment cores and attributed to diagenesis [Muller, 1977;Waples and Sloan, 1980;Waples, 1985] (unfortunately, N and C isotope data were not obtained in these previous studies). A full explanation of these organic geochemical phenomena, and a more comprehensive reconstruction of diagenesis in this section, would require analyses of separated organic and inorganic N fractions (see studies by Muller [1977], Waples and Sloan [1980], and Williams et al [1995]) and a more comprehensive consideration of the chemical compositions of the interstitial waters from the sediment cores.…”
Section: Diagenetic Processessupporting
confidence: 89%
“…On the other hand, OC-rich strata may have relatively high C/N ratios as a result of selective loss of nitrogeneous organic compounds and a relatively limited adsorption capacity of the inorganic matrix. For this reason, whole-rock and kerogen C/N ratios are not strictly comparable, and the whole-rock C/N ratios cannot be used effectively to determine the source or even the relative extent of preservation of the organic matter in ancient sediments [15]. In relatively OC-poor, clay-rich strata, therefore, adsorbed IN might be the predominant form of nitrogen.…”
Section: Diagenetic Effectsmentioning
confidence: 99%
“…In relatively OC-poor, clay-rich strata, therefore, adsorbed IN might be the predominant form of nitrogen. Data of Waples [15] and references summarized within suggest that the clay-rich insoluble residue of most pelagic marine sediments has the capacity to adsorb up to 0.5% by weight of exchangable and free IN. Our lightcolored, bioturbated OC-poor samples contain no more than 0.03% TN, with C/N ratios that average 18.4 (+6.6).…”
Section: Diagenetic Effectsmentioning
confidence: 99%
“…Except for values of 68 and 27 at about 33.8 mbsf, the C/N ratios for sediments at Site 796 are either within or below the range normally found in modern marine sediments (9-18; Müller, 1977). Since the nitrogen component of this ratio includes both organic and inorganic forms, inorganic nitrogen in clay-rich, low-organic carbon sediments can significantly decrease the ratios (Müller, 1977;Waples, 1985). Waples (1985) reported that inorganic nitrogen is the dominant form in Goban Spur (DSDP Leg 80) sediments containing less than 0.50% C org .…”
Section: Carbon Nitrogen and Sulfurmentioning
confidence: 99%
“…Since the nitrogen component of this ratio includes both organic and inorganic forms, inorganic nitrogen in clay-rich, low-organic carbon sediments can significantly decrease the ratios (Müller, 1977;Waples, 1985). Waples (1985) reported that inorganic nitrogen is the dominant form in Goban Spur (DSDP Leg 80) sediments containing less than 0.50% C org . Interpretations of the downhole changes in C/N ratios in Figure 28 are therefore difficult to make due to the abundance of clays and the low organic carbon contents in Site 796 sediments.…”
Section: Carbon Nitrogen and Sulfurmentioning
confidence: 99%